Explanation of a Sustainable Digital Transformation Process in a Firm - Dang, Duong; Vartiainen, Tero; Do, Thai (Springer, 2023)
We are living in the digital era, in which firms often face many challenges due to the rapid development of digital technologies. Thus, firms need to reform their traditional business models by integrating digital technologies into all areas of existing business processes for their survival. This integration process is called digital transformation (DT). However, the understanding of how to develop a sustainable DT process for firms remains incomplete and fragmented. As a result, we studied how DT unfolds over a period of years in the case of telecenters (TCTs) in the context of sustainability. We used a qualitative case study as our research approach. We contribute to the literature by introducing a model of a digital transformation process and its relationship with sustainability. We also contribute to practice by suggesting that in order to ensure sustainability for the long term, managers need to prioritize the sustainable factors in each phase of the DT process while maintaining, continuously seeking, and implementing new digital initiatives.
Keywords: Sustainability; Digital transformation; Telecenters; Case study; fi=Tietojärjestelmätiede|en=Information Systems|